Effects of Delayed Payment on Projects and Stakeholders: A Case Study of Keta Municipal Assembly - Teku, Aaron Yao (2015)
A Thesis submitted to the Department of Building Technology, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of Master of Science in Construction Management, 2014